2015
DOI: 10.1016/j.psyneuen.2014.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal effects of the SSRI paroxetine on salivary cortisol in Major Depressive Disorder

Abstract: Hypothalamic-pituitary-adrenal (HPA)-axis dysregulation is a prominent finding in more severe Major Depressive Disorder (MDD), and is characterized by increased baseline cortisol levels at awakening (BCL), blunted cortisol awakening response (CAR) and increased area under the cortisol curve (AUC). Selective serotonin reuptake inhibitors (SSRIs) appear to normalize HPA-axis dysfunction, but this is hardly investigated longitudinally.We studied salivary BCL, CAR and AUC at awakening and 30 min thereafter. We com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 51 publications
4
31
2
Order By: Relevance
“…a state effect), but are rather a proxy for (the possibility of) successful treatment (Ruhé et al, 2015). For example, as noted before (Ruhé et al, 2015), antidepressants' effect on multidrug resistance p-glycoprotein may be a prerequisite for their clinical effectiveness (Pariante, 2008;Pariante et al, 2004).…”
Section: Trait Vs Statementioning
confidence: 99%
See 1 more Smart Citation
“…a state effect), but are rather a proxy for (the possibility of) successful treatment (Ruhé et al, 2015). For example, as noted before (Ruhé et al, 2015), antidepressants' effect on multidrug resistance p-glycoprotein may be a prerequisite for their clinical effectiveness (Pariante, 2008;Pariante et al, 2004).…”
Section: Trait Vs Statementioning
confidence: 99%
“…a state effect), but are rather a proxy for (the possibility of) successful treatment (Ruhé et al, 2015). For example, as noted before (Ruhé et al, 2015), antidepressants' effect on multidrug resistance p-glycoprotein may be a prerequisite for their clinical effectiveness (Pariante, 2008;Pariante et al, 2004). Given that DHEAS also is a substrate for p-glycoprotein (Bortfeld et al, 2006;Zelcer et al, 2003), the changes in DHEAS during successful antidepressant treatment may not reflect a state-effect, but rather the effective modulation of p-glycoprotein by the antidepressant (Ruhé et al, 2015).…”
Section: Trait Vs Statementioning
confidence: 99%
“…This finding is supported by the work of Harmer et al (2003) who found that six-day administration of citalopram (20 mg/day) brought about significant increases in waking cortisol in healthy volunteers. Interestingly, in depressed patients, SSRIs have been found to lower waking cortisol levels (Knorr et al 2012; Ruhé et al 2015). Since waking cortisol levels may be increased in depression (Bhagwagar et al 2005), the direction of the effect of SSRIs on waking cortisol could be related to mental health status.…”
Section: Discussionmentioning
confidence: 99%
“…However, very few studies have examined this. In patients with major depressive disorder (MDD), and in first-degree relatives of depressed patients, longer-term administration of SSRIs has been found to decrease cortisol AUC and decrease waking cortisol levels (Hinkelmann et al 2012; Knorr et al 2012; Ruhé et al 2015). This small body of work suggests that SSRI treatment affects the pattern of diurnal cortisol secretion in depressed patients and those at risk of depression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation